Letter from Max Bredig to Anny van der Sluys, July 10, 1945 - Bredig, Max Albert (1945)
Max Albert Bredig ( 1902-1977) sends Anny van der Sluys the address of Eva Schnell’s (1913-1944) parents in Brazil. Eva Schnell’s maiden name was Jolowicz.
Keywords: Bredig, Max Albert, 1902-1977; Schnell, Eva, 1913-1944; Schnell, Alfred, 1900-1944; Jolowics, Julius, 1877-1953; Van der Sluys, Anny